Sobre iconografia cristiana, a propòsit dels murals romànics de Santa Maria de Cap d'Aran - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2022)
This paper discusses the mural paintings that decorated the Church of Santa Maria de Cap d'Aran, one of the most important churches in the Vall d'Aran region. The paintings are now dispersed between The Met Cloisters, the Maricel Museum in Sitges and several private collections. The author relates the paintings to the original architecture in order to understand, as far as possible, their iconographic program, looking for the prototypes of some of the images. Likewise, a study is made of a fragment preserved in situ that is of a later date than the rest of the paintings and extensively damaged. Lastly, consideration is given to the irregular history of the removal and sale of the paintings.